Development of The Gotang Game Model Towards Students’ Active Participation of Class V Physical Education Learning - Moh. Alif Arya Ayomi; Agus Pujianto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to develop the GOTANG game model as an alternative for physical education learning to increase the active participation of fifth-grade elementary school students in Semarang City. This research is motivated by students' low in-terest in traditional games and limited facilities and infrastructure in learning large ball games, especially handball. This study used the Research and Develop-ment (R&D) method with the ADDIE model (analysis, design, development, imple-mentation, and evaluation). Data collection was conducted through observation, interviews, and questionnaires. Data analysis used quantitative and qualitative descriptive analysis using the Guttman scale. A small-scale trial was conducted on 15 students from SDN Pakintelan 2, while a large-scale trial was conducted on 45 students from SDN Pakintelan 2 and Pakintelan 3. Product validation involved game experts and physical education experts. The results of the study are as fol-lows: (1)  The validation data according to experts is 97% in the sufficient category. (2) The results of small-scale trials were 92% with Good category, and (3) The re-sults of large-scale trials were 90% in the Good category. The product resulting from this development is a model of the Gobak Sodor Bala Tangan (GOTANG) game that can be assembled and disassembled. The Gotang game has been de-clared suitable for use as a learning model for physical education materials in elementary schools.